Molecular preservation in halite‐ and perchlorate‐rich hypersaline subsurface deposits in the Salar Grande basin (Atacama Desert, Chile): Implications for the search for molecular biomarkers on Mars. Issue 2 (19th June 2013) - Fernández‐Remolar, D. C.; Chong‐Díaz, G.; Ruíz‐Bermejo, M.; Harir, M.; Schmitt‐Kopplin, P.; Tziotis, D.; Gómez‐Ortíz, D.; García‐Villadangos, M.; Martín‐Redondo, M. P.; Gómez, F.; Rodríguez‐Manfredi, J. A.; Moreno‐Paz, M.; et al.
Abstract: [1] Similarities between the Atacama Desert (Chile) and Mars include extreme aridity, highly oxidizing chemistry, and intense ultraviolet radiation that promoted the photochemical production of perchlorates and nitrates. Concentration of these ions under hyperarid conditions led to the formation of nitrate‐ and perchlorate‐bearing deposits in ephemeral lakes, followed by later deposition of chlorides and sulfates. At some locations, such as the Salar Grande, hypersaline deposits have remained unaltered for millions of years. We conducted a drilling campaign in deposits of the Salar to characterize the preservation state of biological molecules. A 5 m deep discontinuous core was recovered and subjected to multitechnique analysis including the antibody microarray‐based biosensor LDChip300 and the SOLID (Signs Of Life Detector) instrument, complemented by geophysical, mineralogical, geochemical, and molecular analysis. We identified two units based on the mineralogy: the upper one, from the surface to 320 cm depth characterized by a predominance of halite and anhydrite, and the lower one, from 320 to 520 cm, with a drop in halite and anhydrite and an enrichment in nitrate and perchlorate. Organic compounds including biomolecules were detected in association with the different depositional and mineralogical units, demonstrating the high capacity for molecular preservation. Hypersaline environments preserve biomolecules over geologically significant timescales; therefore, salt‐bearing materials should be high‐priority targets for the search for evidence of life on Mars. Key Points: Preservation of biomolecules in salty deposits of Atacama Same salty deposits are found in Mars Mars salt‐enriched deposits have a great astrobiological potential